1978
DOI: 10.1002/cber.19781110438
|View full text |Cite
|
Sign up to set email alerts
|

Umsetzungen mit Monohydrazonen von Dicarbonylverbindungen, VI: Synthesen von 4‐Oxocarbonsäuren und deren Estern mit Hilfe von α‐Hydrazonoaldehyden

Abstract: a-Hydrazonoaldehyde (11) sind aus Ketonhydrazonen 14 durch Selendioxid-Oxidation oder durch Kupplung von Enaminen 12 rnit Diazoniumsalzen 13 darstellbar. Mit (Ethoxycarbonyl-methy1en)triphenylphosphoran (15) oder rnit Estern 17 in Gegenwart von Basen lassen sich a-Hydrazonoaldehyde 8, l l zu Hydrazonen ungesattigter 4-Oxocarbonester (16) umsetzen. Durch Hydrolyse oder reduktive Hydrolyse erhalt man ungesattigte bzw. gesattigte 4-Oxocarbonester (18 bzw. 19). Hydrazonoethyliden-Derivate von Ketonen ergeben bei d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

1981
1981
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…The reactivities of compound 47 and its E isomer have been briefly reported on in the literature. [11,15] In addition, we found that Michael additions were observed in good yields with soft carbanions formed from dimethyl malonate, β-keto ester and methyl (phenylsulfonyl)acetate (Scheme 6). The regiospecificities of these additions were deduced from the NMR spectra of the compounds and were consistent with previously published results.…”
Section: B) Reactivities Of γ-Aryl βγ-Unsaturated Hydroxamatesmentioning
confidence: 94%
See 4 more Smart Citations
“…The reactivities of compound 47 and its E isomer have been briefly reported on in the literature. [11,15] In addition, we found that Michael additions were observed in good yields with soft carbanions formed from dimethyl malonate, β-keto ester and methyl (phenylsulfonyl)acetate (Scheme 6). The regiospecificities of these additions were deduced from the NMR spectra of the compounds and were consistent with previously published results.…”
Section: B) Reactivities Of γ-Aryl βγ-Unsaturated Hydroxamatesmentioning
confidence: 94%
“…The regiospecificities of these additions were deduced from the NMR spectra of the compounds and were consistent with previously published results. [11,15] With butyllithium, addition at the ketone function of 47 was observed and alcohol 51 was obtained. With other lithium derivatives (MeLi, tBuLi) and with Grignard reagents, complex reaction mixtures were observed [formation of alcohols and (or) Scheme 6.…”
Section: B) Reactivities Of γ-Aryl βγ-Unsaturated Hydroxamatesmentioning
confidence: 97%
See 3 more Smart Citations